Turkish community pharmacists' behavioral determinants in provision of pharmaceutical care to elderly patients - OKUYAN, BETÜL; SANCAR, MESUT (SPRINGER, 2021)
Background It is crucial to develop and implement community pharmacist-led pharmaceutical care services in primary care that could prevent and detect potentially inappropriate prescribing and promote medication adherence in older patients. Objective The aim of this study was to determine community pharmacists' perceived barriers and facilitators face during the provision of pharmaceutical care to older patients by using a theoretical domains framework. Method A cross-sectional online survey was conducted among community pharmacists in Turkey. A Turkish version of the 50-item Determinants of Implementation Behavior Questionnaire was developed to evaluate behavioral determinants of community pharmacists on delivering pharmaceutical care to older patients. Main outcome measures The behavioral determinants of community pharmacists. Results A total of 354 community pharmacists answered the questionnaire. The mean age was 43.2 (standard deviation = 11.1), and 227 (64%) of the pharmacists were female. Community pharmacists' positive opinions on pharmaceutical care service outcomes in older patients and feedback were regarded as facilitators. Community pharmacists' motivational level and emotions were additional determinant facilitators in delivering pharmaceutical care to older patients. Their negative opinions on the impact and action of pharmaceutical care in older patients were regarded as barriers. Conclusion In primary health care, a theory-based e-distant training program for community pharmacists and the guidelines for standard pharmaceutical care services led by community pharmacists could be designed by addressing barriers related to the impact and action of pharmaceutical care in older patients.
Keywords: Behaviors; Community pharmacist; Older patient; Pharmaceutical care; Primary care; Theoretical domains framework; CROSS-SECTIONAL SURVEY; COGNITIVE SERVICES; OLDER-PEOPLE; EDUCATION; CONSENSUS